Use of antikeratin antibodies to distinguish between rheumatoid arthritis and polyarthritis associated with hepatitis C infection - A. Kessel; I. Rosner; E. Zuckerman; T.D. Golan; E. Toubi (PAGEPress Publications, 2001)
Objective: To investigate whether antikeratin antibodies (AKA) could be usefull in the differential diagnosis of patients with rheumatoid arthritis (RA) compared to patients with hepatitis C virus (HCV) associated polyarthritis, who are seropositive for rheumatoid factor (RF). Methods: AKA were assayed in 3 different groups of patients; all were RF seropositive: Group 1: 25 patients with HCV associated polyarthralgia or arthritis. Group 2: 33 patients with RA. Group 3: 13 patients with autoimmune disorders other than RA. Fifteen healthy individuals served as controls. Results: AKA were detected in 20/33 patients with RA (60.6%) compared to only 2/25 patients (8%) with HCV associated arthritis (p < 0.0001). AKA were observed in 2/13 patients of Group 3 (15.3%). These results were also statistically different from those of patients with RA (p = 0.008). AKA were not found in the sera of the healthy controls. Conclusion: AKA is a useful marker to differentiate patients with RA from those with hepatitis C arthritis.